Rediscovering one’s own voice in a brief psychoanalytic group intervention aimed at malignant mesothelioma patients and their families - Franzoi, Isabella Giulia (Frontiers in Psychology, 2024)
Occupational and/or environmental exposure to asbestos can lead to clinical manifestation of a variety of diseases, including malignant mesothelioma (MM), a rare cancer with a particularly high incidence rate in areas with a long history of asbestos processing. This paper aims to describe brief psychoanalytic groups (BPGs), which is an intervention model aimed at MM patients and their families in the early stages of the disease, shortly after diagnosis. The BPG model comprises 12 weekly sessions of 1 h each, co-led by two psychoanalytically oriented psychotherapists who are trained in working with cancer patients and their families and in the specifics of the BPG setting. Reflections in this paper on the BPGs will attempt to trace the voice of the group in clinical material, paying attention to its horizontal unfolding as a melodic development over time and its vertical unfolding as a harmonic interweaving between the different individual voices, which, even when opposed to each other, can find a generative interlocking of meaning. In the BPG, then, it is possible to set in motion transformations that allow one to embrace the different and diverse affective colorations of experience, evolve toward a thinking that is capable of incorporating intense emotions related to death and grief, follow healthier paths of interaction on an intrapsychic and interpersonal level, and find traces of one’s own vitality.